AN EVALUATION OF ENGLISH TEXTBOOKS LIFE PRE-INTERMEDIATE AND ENGLISH FILE PRE-INTERMEDIATE IN THE PERSPECTIVES OF CULTURAL, POLITICAL AND LANGUAGE TEACHING ASSUMPTIONS (Journal of Foreign Language Studies, 2020)
The National Foreign Languages Project (the Project 2020/the Project) has required Vietnamese universities to implement various changes to improve the delivery of their English programs. Given the importance of textbook in this implementation, this study evaluates the two textbooks: Life (recommended by the Project 2000) and English File (well-known for its communicative approach to language teaching) to determine one suitable for the context of the University of Fire Prevention and Fighting (UFPF). The study assessed the two books using a framework which allows the evaluator to assess not only cultural and ideological assumptions but also language teaching and learning issues. The findings provide a foundation for the university’s choice of a textbook that meet the requirements of the Project, learners and other factors. Implications of the study are also discussed in the article.
Keywords: English File; Life; textbook evaluation; material evaluation; Project 2020